Conservative approach for the management of bilateral pneumothorax and pneumomediastinum after laparoscopic totally extraperitoneal inguinal hernia repair - Omeroglu, Sinan; Guven, Onur; Kostek, Mehmet; Tufan, Aydin Eray; Baran, Elif (Journal of the Pakistan Medical Association, 2023)
Laparoscopic totally extraperitoneal inguinal hernia repair is considered a common and safe procedure. Here, we present the case of a 31-year-old male with right indirect inguinal hernia and no medical history. The patient underwent laparoscopic totally extraperitoneal inguinal hernia repair and the operation was completed successfully. During extubation, subcutaneous emphysema was noted at the neck, chest, and above the nipples. Tracheal injury was excluded by the anaesthesiologists and otorhinolaryngologists. On arterial blood gas, the patient's oxygen saturation was 95% with nasal oxygen support. The patient was followed-up closely in the general surgery inpatient clinic. Computed tomography was performed, on which bilateral pneumothorax and pneumomediastinum were noted. Conservative management was planned and the patient was discharged on the fourth postoperative day. Laparoscopic totally extraperitoneal inguinal hernia repair is considered a routinely applied safe procedure, however, appropriate care should be taken to avoid possible complications. Keywords: Laparoscopy, Inguinal Hernia, Pneumothorax, Pneumomediastinum.